Novel vegan ice cream made from red kidney bean milk with a probiotic: Technological and biofunctional characteristics - Acar, Emine Beyda; Karahan, Talha; Mutlu, Dora; Sagdic, Osman; Ozturk, Hale Inci (WILEY, 2025)
This study aimed to develop functional vegan ice creams (ICs) using red kidney bean milk (RKBM), with (RP) and without (R) probiotics (Bacillus coagulans ATCC 7050), and to compare their physicochemical, functional, and sensory properties with dairy counterparts. The IC samples had a dry matter content of 33.80%-35.54% and a protein content of 2.05%-2.20%. Although the brightness of the vegan samples was lower compared to dairy samples, the vegan samples were characterized by more reddish and yellowish hues. The vegan samples provided higher overrun values (36.00%-37.50%) compared to the dairy ones. Besides, the vegan samples exhibited higher antioxidant activity (5224-6148 mu M Trolox equivalent antioxidant capacity/g) and total phenolic content (TPC) (72.98-184.75 mg gallic acid equivalent/100 g). The processes of ripening, fermentation, and freezing led to an increase in TPC values of all samples. The highest probiotic viability (7.52 log10CFU/g) was observed in the RP mix, but a decrease in probiotic cell count occurred after freezing. The vegan ICs received lower sensory scores than the dairy samples. Despite lower sensory scores, RKBM-based ICs demonstrated suitable functional and technological properties, suggesting that RKBM has significant potential for use in functional vegan food products. Further studies are needed to improve sensory acceptability.
Keywords: functional food; Phaseolus vulgaris; phenolic content; plant milk; spore former probiotic; PHASEOLUS-VULGARIS L.; OF-BACILLUS-COAGULANS; ANTIOXIDANT ACTIVITIES; PROFILE; ALTERNATIVES; VIABILITY; YOGURT; WHITE; Food Science & Technology